2005
DOI: 10.3748/wjg.v11.i41.6538
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of 8-Br-cAMP on differentiation and apoptosis of human esophageal cancer cell line Eca-109

Abstract: The differentiation and apoptosis of human esophageal cancer cell Eca-109 can be induced after 24- and 48-h treatment with 8-Br-cAMP, respectively. Upregulation of wt p53, iNOS and downregulation of c-myc may be associated with differentiation and apoptosis of Eca-109 cells. Furthermore, upregulation of FasL, p38 kinase and caspase-3 as well as downregulation of bcl-2, and Fas may be involved in the apoptosis of Eca-109 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Contributing mechanisms include G1 and G2/M cell cycle arrest (Ogawa, et al, 2002), mitochondrial depolarization, release of cytochrome c into the cytosol, and caspase-9 and -3 activation (Moon and Lerner, 2003). Elevation of cAMP concentration has also been shown to inhibit cell growth and induce apoptosis in other cancer cell lines such as retinoblastoma cells (Fassina, et al, 1997), papilloma cells (Marko, et al, 1998), glioma cells (Chen, et al, 2002), neuroblastoma cells (Kumar, et al, 2004), and esophageal cancer cells (Wang, et al, 2005). In cancer cell lines this effect of PDE-IV inhibition is an obvious area of interest since halting growth of these cells is a much-desired therapeutic goal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contributing mechanisms include G1 and G2/M cell cycle arrest (Ogawa, et al, 2002), mitochondrial depolarization, release of cytochrome c into the cytosol, and caspase-9 and -3 activation (Moon and Lerner, 2003). Elevation of cAMP concentration has also been shown to inhibit cell growth and induce apoptosis in other cancer cell lines such as retinoblastoma cells (Fassina, et al, 1997), papilloma cells (Marko, et al, 1998), glioma cells (Chen, et al, 2002), neuroblastoma cells (Kumar, et al, 2004), and esophageal cancer cells (Wang, et al, 2005). In cancer cell lines this effect of PDE-IV inhibition is an obvious area of interest since halting growth of these cells is a much-desired therapeutic goal.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in the treatment of bronchial asthma, PDE inhibition is thought to be an important mechanism of the anti-inflammatory actions of theophylline. Theophylline and rolipram have been shown to increase eosinophil intracellular cAMP concentrations and inhibit eosinophil survival (Momose, et al, 1998, Takeuchi, et al, 2002, Wang, et al, 2005). Recently it has been demonstrated that cAMP elevation resulted in significant inhibition of colony growth and induced apoptosis of progenitor cells in asthmatics, but not in normal subjects.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to inhibit proliferation, induce differentiation and apoptosis in a malignant glioma cell line (A-172) and an esophageal cancer cell line (Eca-109) [36,37]. Modulation of the cAMP/PKA pathway may thus represent a possible target site for treating malignant tumors and 8-Br-cAMP meets this criteria in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Among PGE2 receptors, PTGER2 has the most potential for elevating intracellular cAMP concentrations (Regan, 2003). Since elevated levels of cAMP are associated with decreased proliferation and increased differentiation or apoptosis in several types of cells including glioblastoma cells (Chen et al, 1998), esophageal squamous cell carcinomas (Wang et al, 2005b), and hippocampal cells (Takadera et al, 2004), we speculate that PTGER2-mediated production of intracellular cAMP may contribute to the growth-inhibitory effect of restored PTGER2 in NB cells lacking endogenous expression of the gene. In our experiments a PTGER2-specific agonist increased intracellular cAMP levels and exerted growth inhibitory effects, at least partly by inducing apoptosis, in stable PTGER2 transfectants established from the SJ-N-CG cell line, although G 0 -G 1 arrest but not apoptosis was predominantly observed in PTGER2 transfectants under low-serum condition without butaprost treatment.…”
Section: Discussionmentioning
confidence: 99%